2007
DOI: 10.1007/s12013-007-0027-4
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized composite islet-kidney transplantation in a miniature swine model

Abstract: Previous work from this laboratory has demonstrated that transplantation of allogeneic thymic tissue as part of a composite vascularized graft is far more successful in terms of both engraftment and long-term survival than transplantation of thymic tissue or cells alone. We have subsequently extended this concept to transplantation of allogeneic islets, comparing survival of islet cell suspensions to that of vascularized composite islet-kidneys (IK), prepared by injection of autologous islets underneath the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It has been shown that many approaches can enhance thymopoieses including: administration of hormones and cytokines (growth hormone, prolactin, ghrelin, keratinocyte growth factor, vitamin D, and IL-7), androgen ablation, caloric restriction, bone marrow transplantation, and thymic tissue transplantation [131140]. In the future, gene therapy and stem cell transplants may yield even better results.…”
Section: Modulation Of the Aged Immune Systemmentioning
confidence: 99%
“…It has been shown that many approaches can enhance thymopoieses including: administration of hormones and cytokines (growth hormone, prolactin, ghrelin, keratinocyte growth factor, vitamin D, and IL-7), androgen ablation, caloric restriction, bone marrow transplantation, and thymic tissue transplantation [131140]. In the future, gene therapy and stem cell transplants may yield even better results.…”
Section: Modulation Of the Aged Immune Systemmentioning
confidence: 99%
“…Kin et al (5) has shown that transplantation of NICC allografts into 15-to 25-kg pigs can achieve normoglycemia, but IVGTT was significantly inferior to nonpancreatectomized animals. In a separate study, syngeneic adult pig islets transplanted under the renal capsule as an islet-kidney composite grafts were capable of reversing diabetes but detailed studies of islet graft function were lacking (16). A more recent study successfully reversed diabetes for over a year after transplantation of intraomental embryonic pig pancreatic tissue in two cynomolgus monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…To test this idea in an in vivo, preclinical, large animal model, we utilized an established model of vascularized islet transplantation in the miniature swine (23-25). Our previous work in the miniature swine showed that autologous transplantation of islets underneath the renal capsule leads to stable, long-term islet engraftment, and production of a composite organ that we have called an islet-kidney (IK).…”
Section: Introductionmentioning
confidence: 99%